PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER ( NHT ) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 002 SINTONG - Indah Kardina; Otang Kurniaman; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The implementation of cooperative learning model Numbered Head Together (NHT) is very helpful in the learning process and the delivery of learning materials. The purpose of research is to improve learning outcomes IPS third grade students of SDN 002 Sintong on the subject matter of these kinds of jobs. This study was conducted in 002 Sintong SDN. This research is a classroom action research (PTK) using 2 cycles of Suharsimi Arikunto, instruments used to collect data is the observation sheet teacher and student observation sheet consisting of 6 statement filled out by observers. I then performed UH to 25 elementary students in the form of an objective matter held in SDN 002 Sintong. Data were analyzed and the results did not reach KKM 6 people, 19 people reached the KKM with the amount of the total value in 1850 with a percentage of 74% with UH Baik.Hasil category II increased by 10.6% from the first UH with a total value of 2065 with a percentage of 82.6% with a Very good category. Key Word : Numbered Head Together, learning outcomes IPS